Three-Dimensional Semiautomatic Road Extraction From a High-Resolution Aerial Image by Dynamic-Programming Optimization in the Object Space - Dal Poz, Aluir Porfírio [UNESP]; Gallis, Rodrigo A. B. [UNESP]; da Silva, Joao F. C. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2010)
This letter proposes a method for 3-D semiautomatic road extraction from a single image by dynamic programming (DP), which requires a form of relief representation such as digital terrain model. Unlike traditional DP methodologies, this method relies on the DP algorithm to carry out the optimization process in the object space rather than in the image space. Road features are traced in the object space, implying the need for a rigorous mathematical model between image-and object-space points. The operator must measure a few seed points in the image space to coarsely describe the roads, which are then transformed into object space to initialize the DP optimization process. The results showed that the method usually works properly, even in the presence of anomalies along roads.
Keywords: Dynamic programming (DP); feature extraction; image analysis; remote sensing